Blood Cell An Overview of Studies in Hematology - Moschandreou, Terry E. (IntechOpen, 2012)
The editor has incorporated scientific contributions from a diverse group of leading researchers in the field of hematology and related blood cell research. This book aims to provide an overview of current knowledge pertaining to our understanding of hematology. The main subject areas will include blood cell morphology and function, the pathophysiology and genetics of hematological disorders and malignancies, blood testing and typing, and the processes governing hematopoiesis. Blood cell physiology, biochemistry and blood flow are covered in this book. This text is designed for hematologists, pathologists and laboratory staff in training and in practice. The work presented in this book will be of benefit to medical students and to researchers of hematology and blood flow in the microcirculation.This book is written primarily for those who have some knowledge of chemistry, biochemistry and general hematology. The authors of each section bring a strong clinical emphasis to the book.